The Driving Factors of Transaction Behavior for Shoe Cleaning Services Through Social Commerce Platforms - Desak Made Febri Purnama Sari; I Putu Abdi Putra Budiartha; Ida Ayu Oka Martini; Putu Ayu Titha Paramita Pika (Universitas Warmadewa, 2025)
This study discusses the phenomenon of the increasing use of social commerce platforms, such as Instagram, by shoe cleaning service providers to promote and sell their services. The trend shows that more consumers are shifting from traditional methods to digital platforms to search for services and conduct transactions. Therefore, this study aims to identify the factors driving transaction behavior for shoe cleaning services through social commerce platforms like Instagram. The research method used is quantitative data analysis involving 314 consumers who made transactions at nine shoe cleaning service brands in Bali province. The data were analyzed using Confirmatory Factor Analysis (CFA) in the SPSS version 25 program. The results of the data analysis indicate that from the 36 indicators initially tested, four main factors were identified that explain the drivers of transaction behavior for shoe cleaning services through social commerce platforms, namely